2015
DOI: 10.1016/j.ymgmr.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress parameters of Gaucher disease type I patients

Abstract: Enzymatic deficiency in Gaucher disease (GD) patients may induce a cascade of events, culminating in secondary effects such as the production of reactive oxygen species (ROS). Detoxification through biological systems which remove or repair the damage may cause the production of peroxides and free radicals that damage all cell components, including proteins, lipids and ADN. The study's aim was the test, using the analysis of plasma samples' the use of lipid peroxidation by thiobarbituric acid reactive substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…The data found in TBARS, corroborated by the literature, shows the difference in the values between the groups studied [26]. These results confirm the findings obtained by this group in a previous study [31], which also showed no significant difference in the parameter between patients with Gaucher's Disease and healthy controls, showing that the cells seem to use another form of stress management in patients with enzyme deficiency.…”
Section: Resultssupporting
confidence: 89%
“…The data found in TBARS, corroborated by the literature, shows the difference in the values between the groups studied [26]. These results confirm the findings obtained by this group in a previous study [31], which also showed no significant difference in the parameter between patients with Gaucher's Disease and healthy controls, showing that the cells seem to use another form of stress management in patients with enzyme deficiency.…”
Section: Resultssupporting
confidence: 89%
“…While a certain level of ROS is essential for the regulation of cell growth and various biological functions, a disrupted ROS balance has negative implications. For example, oxidative stress has been associated with a number of pathological conditions, including neurodegenerative disorders (1318), skeletal muscle disorders (1923), lysosomal storage disorders (24, 25), cardiomyopathy (26, 27), carcinogenesis (28, 29), atherosclerosis (30, 31), diabetes (32, 33), and aging (34, 35). While the involvement of oxidative stress is firmly demonstrated in these pathological conditions, the specific source of ROS generation and the mechanisms by which each disease is regulated by ROS has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…However, alterations in other markers were less conclusive and untreated individuals were not evaluated. Mello et al reported that, on average, SOD and catalase activities were higher in ten treatment naïve GD1 patients (age range 3–46 years) when compared to healthy controls [ 19 ]. However, they did not observe any differences in MDA and protein carbonyl levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that these chronic complaints may reflect unabated inflammation associated with release of pro-inflammatory cytokines and other mediators either directly from Gaucher macrophages or indirectly by crosstalk between Gaucher cells and immunomodulatory lymphocytes [ 12 , 24 , 25 ]. However, it has also been hypothesized that accumulation of toxic glycosphingolipids within cells leads to the production of reactive oxygen species (ROS) and an imbalance between the pro-oxidants and the antioxidant reserve, resulting in oxidative stress and inflammation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation